The Role of Binary Settings in John Updike’s Short Stories: A Structuralist Approach: مؤيد انوية ججو الجماني (Journal of the College of Education for Women, 2021)
John Updike’s use of setting in his fiction has elicited different and even conflicting reactions from critics, varying from symbolic interpretations of setting to a sense of confusion at his use of time and place in his stories. The present study is an attempt at examining John Updike’s treatment of binary settings in Pigeon Feathers and Other Stories (1962) to reveal theme, characters’ motives and conflicts. Analyzing Updike’s stories from a structuralist’s perspective reveals his employment of two different places and times in the individual stories as a means of reflecting the psychological state of the characters, as in “The Persistence of Desire”, or expressing conflicting views on social and political issues, as in “A&P” and “Home”, or commenting on religious issues as in “Pigeon Feathers.” The study also examines Updike’s use of setting as a structural device to provide unity to the diverse stories in the collection. The study concludes that binary settings provide structural unity to the stories in the collection and add a psychological dimension and depth to the characters.